Pengaruh Perkembangan Kota Singapura terhadap Angka Pengungkapan Penyelundupan Barang Palsu di Pelabuhan PSA Singapura - Ariobowo, Mahadika; Putranti, Ika Riswanti; Farabi, Nadia (Journal of International Relations, 2017)
This research is aiming to know the impact of the implementation of ACFTA, such as the raising of trade activity in PSA Singapore and the raising of illicit counterfeit goods in PSA Singapore, as well as to know the cause of its problems. In this research, Statistic Criminal Theory used to determine the relation between Illicit Counterfeit Goods with City Development of Singapore. The method of this research is explanative by appointing one problem and focusing on the cause of the problem. The outcome of the research is that there is a relation between the illicit counterfeit goods with trade agreement and the city development of Singapore with the use of City Development Index from UN-HABITAT 1998 as a measurement. This research also found that the more developed and advanced a city, the more vulnerable a city would be towards criminality.